Aromatase Inhibitor Letrozole in Synergy With Curcumin in the Inhibition of Xenografted Endometrial Carcinoma Growth. Issue 7 (1st October 2009) - Liang, Yuan-Jiao; Hao, Qun; Wu, Yuan-Zhe; Wang, Qiao-Lian; Wang, Jian-Dong; Hu, Ya-Li
Abstract : Objective: Endometrial carcinoma is a malignant tumor in the uterus. Its current treatment is not satisfactory. The present study aimed to promote the inhibitory effect on the implanted endometrial tumor growth. Methods: Nude mice were implanted with endometrial carcinoma. Some tumor-laden mice were treated with aromatase inhibitor letrozole and/or curcumin. The tumor growth was monitored. Tumor cell apoptosis was detected in both control and treated groups. Results: Fifty mice were successfully implanted with the endometrial tumor. Treatment with letrozole markedly inhibited the tumor growth; the inhibitor effect was further strengthened by combination with letrozole and curcumin. The results also showed that letrozole enhanced the expression of Bax and cytochrome c release and suppressed the expression of estrogen receptor in tumor cells. Treatment with curcumin inhibited the expression of Bcl-2 in tumor cells at the mRNA and protein levels. Tumor cell apoptosis was observed in mice treated with either letrozole or curcumin; however, combination of letrozole and curcumin further enhanced the inhibitory rate in tumor growth. Conclusions: Treatment with either letrozole or curcumin could inhibit the xenografted endometrial tumor growth via inducing apoptosis in tumor cells. Combination of letrozole and curcumin further strengthened the inhibitory effect on tumor growth.